O10.5 Rapid diagnosis of trichomonas vaginalis by testing vaginal swabs in an isothermal helicase-dependent amplivue® assay. (13th September 2015) - Chernesky, M; Gaydos, C; Marrazzo, J; Hobbs, M; Schwebke, J
Abstract : Introduction: Infections due to Trichomonas vaginalis are treatable. Diagnostic methods such as wet mount microscopy are rapid but insensitive. Culture or traditional molecular assays are more sensitive but lack rapid results. Biohelix (a Quidel company) has created an isothermal, cassette-based, point-of-care molecular amplified test for the diagnosis of T. vaginalis in vaginal samples which can provide a diagnosis in 5 min. The objective was to demonstrate the clinical performance of the AmpliVue ® Trichomonas assay on vaginal swabs from women with or without symptoms living in 5 geographical areas of North America. Methods: Women attending STD, family planning, colposcopy and OB/GYN clinics were invited to participate using an investigational research board approved consent form. A healthcare worker collected 4 swabs. The first and second swabs were randomised for wet mount and culture (In-Pouch system, Biomed Diagnostics). Cultures were inoculated and read at 2 and 3 days, and wet mount microscopy performed within 1 h of collection. The third was tested in AmpliVue ® and the fourth in Aptima TV (ATV; Hologic, Inc), a transcription-mediated amplification assay. AmpliVue ® and ATV testing was performed within 48 h. Positives by diagnostic method were compared to each other and agreements with kappa values were calculated between AmpliVue ® and ATV. Results: A total of 1132 women (373 symptomatic and 759 asymptomatic) were enrolled. Comparing AmpliVue ® to culture and wet mount as a patient infected status demonstrated 100% sensitivity, 98.2% specificity and 87.9–100% positive and negative predictive values in patients with or without symptoms. AmpliVue ® showed strong overall agreement with ATV (97.5% 0.89 kappa). Conclusion: The AmpliVue Trichomonas Assay identified substantially more T. vaginalis infections and yielded accurate results in 45 min for the diagnosis and treatment of Trichomonas vaginalis in symptomatic and asymptomatic patients representing high and low-prevalence clinics. Clinicians can use this information for their clinics. Disclosure of interest statement: Dr. Chernesky has received research funding from Quidel.